Recent Implementation of Malaysian National Axle Load Policies via Weight Restriction Orders 1989, 2003 and 2017 - Shahruddin, M. N.; Lim, C. C.; Ng, S. K.; Mahamud, K. M. S. Ku; Uzir, M. H. (New Approaches in Engineering Research Vol. 8, 2021)
Bridges in Malaysia were built to various standards in terms of bridge loading since the early 1900s. Axle Load Study in 1987 was conducted due to doubt in the existing bridge capacity to carry the current traffic load at the time. The study had led to the formulation of Weight Restriction Order (WRO) 1989 for truck legal axle weights based on Short Term Axle Load (STAL) policy, which considers HA loads with no checking done on HB load. This comprised the nation’s bridges constructed before 1972. Medium Term Axle Load (MTAL) policy was later implemented in 2003 by the introduction of WRO 2003. MTAL are loadings derived from HA load or 45 units HB loading guided along the centreline. This comprised the nation’s bridges constructed from 1972 onward. Several other studies had also been conducted in the effort to come out with Malaysian design loads for bridges. Indeed, an axle load study was conducted in 2016 to investigate the possibility of a new axle load policy. A new assessment load model to evaluate existing bridge carrying capacity is proposed in the study. The findings were accordingly gazetted in 2017 with the issuance of WRO 2017. Oblivious of these studies, many Malaysian engineers today are not informed of the rationales or basis of the practices, especially those related to bridge assessment. The purpose of this paper is to revisit these studies and discuss pertinent decisions made with regard to the national axle load policies, which were implemented through the issuance of WRO 1989, WRO 2003 and WRO 2017.